HUBUNGAN INTENSITAS PENGGUNAAN SOFTWARE PLECO DENGAN PENGUASAAN KOSAKATA BAHASA MANDARIN PADA MAHASISWA SEMESTER VI STBA-PIA MEDAN 常用 PLECO 软件与汉语词汇掌握能力的相关性研究 —— 以亚院三年级学生为列 - Paulia, Paulia (Journal of Language, Literature and Teaching, 2023)
This study aimed to analyze the correlation between the intensity of using Pleco application and the Chinese vocabulary mastery among the third grades / 6 semestre students of the Asia International Friendship College. This research is a quantitative research with a non-experimental design, called the correlational quantitative method. This research adopted the cluster random sampling method, and used the test paper to investigate the students’ frequency of usage of Pleco software and their Chinese vocabulary mastery. The population of this study amounted to 93 persons of students of STBA-PIA from the sixth semestre and this research will take 30 students as a sample, the sample was taken by using the Cluster Random Sampling technique. The instrument of research was built in the form of a questionnaire with 12 items and 20 test questions. Due to the International standard of HSK questions, the test is declared valid. The reliability test of the questionnaire used the Alfa Cronbach formula which got the results of r was 0.7 so it was categorized as high. and the test also considered reliable. The statistic of paper test results showed that the mean score of third grades students of the Asia International Friendship College commonly used Pleco was 78.3 and the average score of students' vocabulary mastery was 81.3. According to the statistic result, it showed that the correlation test result is 0.62, and the t-test value appeared to be bigger than the t-distribution value (4.2 bigger 1.70), which indicated that there is a significant connection between the common usage of Pleco software and Chinese vocabulary mastery by the sixth semester students of Asia International Friendship College. Keywords: Pleco, Chinese Vocabulary, Mastery, Intensity.